EMPLOYERS’ LEVEL OF SATISFACTION ON THE WORK PERFORMANCE OF DE LA SALLE UNIVERSITY-DASMARIÑAS UNDER THE COLLEGE OF BUSINESS ADMINISTRATION AND ACCOUNTANCY (CBAA), COLLEGE OF EDUCATION(COEd), COLLEGE OF LIBERAL ARTS AND COMMUNICATIONS (CLAC), AND COLLEGE O - VALERA, FELINORE ANGELICA; Mercado, Edna; Salibay, Cristina (12th International Scholars Conference 2025, 2026)
This study assessed employer satisfaction with the work performance of graduates from De La Salle University-Dasmariñas (DLSU-D), specifically from the College of Business Administration and Accountancy (CBAA), College of Education (COEd), College of Liberal Arts and Communications (CLAC), and College of Science and Computer Studies (CSCS). Researchers surveyed 27 employers across education, government, and private sectors. Most surveyed employers held supervisory or managerial roles and had hired DLSU-D graduates in diverse fields like education, human resources, IT, finance, and health sciences. Employers reported high satisfaction with graduates' mastery of knowledge, technical skills, and interpersonal abilities, especially noting their work ethics, dedication, and adaptability. While the overall performance and preparedness of graduates were highly rated, the study identified areas for improvement, including communication skills, punctuality, and initiative. The findings emphasize the need to align academic training with industry expectations, highlighting that DLSU-D graduates significantly contribute to organizational success. Recommendations include enhancing soft skills development, updating curricula based on employer feedback, and strengthening career readiness programs to further improve graduate outcomes.